P PENGARUH MASSAGE PUNGGUNG TERHADAP KELANCARAN ASI PADA IBU POSTPARTUM DENGAN SECTIO CAESAR - Farhandika Putra; Siti Rukayah (LPPM Universitas Sari Mulia, 2020)
Background: Mothers who deliver by SC are at 3 times greater risk of experiencing barriers to breastfeeding compared to normal birth. WHO sets the indicator of SC delivery at 5-15% for each country, if not according to indications SC surgery can increase the risk of morbidity and mortality in mothers and babies. One of the efforts to stimulate prolactin and oxytocin hormones that play a role in the smoothness of breast milk is back massage.Objective: to determine the effect of back massage on breast milk fluency in postpartum mothers with SC.Methods: This study used quasi-experimental method with pretest and posttest without control group design. The samples in this study were 11 patients with accidental sampling technique. The instrument in this study was a breast milk fluency questionnaire.Results: before the back massage, the respondents who experienced non-fluent breast milk were (100%) and after the back massage, the respondents who experienced fluent breast milk were (81.8%). The results of the Wicoxon signed rank test obtained a P value of 0.004 (<0.05) H0 rejected Ha accepted.Conclusion: there is an effect of back massage on breast milk fluency in postpartum mothers with SC. It is recommended for respondents to routinely do back massage to increase breast milk fluency.